Residential Spatial Arrangement Patterns in Ari Nur's Novel Memory Dilation - Rofifah Indah Sari Dzakiyah Putriana; Alfian Ari Wijaya; Eva Dwi Kurniawan (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2023)
Buildings are a form of architecture that has an important role in life. Residential architecture such as a house is one of human needs and a manifestation of the understanding of the function, ideas, and behavior of its occupants. In designing a house it is very important to determine the pattern of spatial arrangement. The problem that exists is how the spatial arrangement pattern of a residential house is adapted to the function and nature of the room which can provide comfort to the occupants. This research aims to see the spatial order patterns contained in the novel Dilatasi Memori by Ari Nur. The way to collect data/analysis information is by reading the novel as a whole, and then taking quotations from sentences related to the components of residential spatial layout patterns in architecture. The spatial arrangement pattern should be a space that has benefits and is influenced by the activities and character of the occupants which will influence the division of space, choice of colors, and furniture. From this research, it can be seen how the pattern of spatial arrangement in the novel Dilatasi Memori by Ari Nur contains several zones that are adapted to their function, namely Public Area, Private Area, Semi-Private Area, and Service Area.